Anjuran Peduli Sosial dalam Al-Quran - Romi Fitriyah; Fuad Al-Mubaroq; Ana Rahmawati (Jurnal Ilmiah Al-Furqan: Al-qur’an Bahasa dan Seni, 2026)
This study examines various Qur’anic exhortations regarding social compassion as a response to the declining sense of social responsibility in contemporary society. The purpose of this research is to identify and analyze Qur’anic teachings related to acts of social care through verses that emphasize attention to vulnerable groups. This research employs a library-based method, utilizing both thematic (Tafsir Maudhu’i) and comparative (Tafsir Muqāran) approaches. The study compares the interpretations of Tafsir Al-Misbah and Tafsir Ibn Kathir concerning Surah Al-Fajr, verses 15–18, which highlight the importance of caring for orphans and feeding the poor. Furthermore, Surah Al-Baqarah, verses 254 and 261, underscore the significance of giving charity sincerely before the Day of Judgment and promise multiplied rewards for those who give without fear or hesitation. Surah Al-Ma’un, verses 2–3, also condemn those who neglect orphans and refuse to assist the needy. The findings indicate that the Qur’an consistently emphasizes social compassion as a fundamental aspect of faith and moral conduct, making these values highly relevant for strengthening social character in the modern era.